Mind, Brain, and Neuroscience - Stapp, Henry P. (Cosmos and History: The Journal of Natural and Social Philosophy, 2014)
<!--[if gte mso 9]> <![endif]-->Quantum mechanics as conceived by Niels Bohr and formulated in rigorous terms by John von Neumann is expressed as quantum neuroscience: a description of the relationship between certain conscious experiences of an observer that are described in terms of the concepts of classical physics and neural processes that are described in terms of the concepts of quantum physics. The theory is applied to recent neuroscience data to determine the rapidity of the observer's probing actions that is needed to account for the capacity of a person's mental intentions to influence that person's bodily actions in the intended way. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->